Pengaruh Kompetensi dan Pelatihan Terhadap Kinerja Perawat Instalasi Bedah Sentral di Rumah Sakit Umum Daerah Ciawi Kabupaten Bogor - Topan Andrian; Adriza; Widya Nengsih (Masyarakat Ekonomi Syariah Bogor, 2025)
The performance of nurses in the Central Surgery Installation (Instalasi Bedah Sentral/IBS) is a crucial factor in ensuring the quality of healthcare services in hospitals. However, there is still a discrepancy between workload and the achievement of optimal performance, which is suspected to be related to competence and training effectiveness. This study aims to analyze the influence of competence and training on the performance of nurses in the Central Surgery Installation of Ciawi Regional Public Hospital (RSUD Ciawi), Bogor Regency. The research method used is quantitative with a survey approach. The population in this study consisted of all nurses in the IBS of RSUD Ciawi, totaling 150 individuals, with 100 respondents selected proportionally. Data collection was conducted through questionnaire distribution. Data analysis techniques included descriptive and inferential statistics using multiple regression, correlation, and the coefficient of determination. The results show that the nurses’ competence is generally categorized as very good, with a correlation coefficient (R) value of 0.608, indicating a strong relationship between competence and performance. The coefficient of determination (R²) value of 0.370 indicates that 37% of the performance variation is influenced by competence. Furthermore, the training received by nurses is generally good and has a strong relationship with performance, with a correlation coefficient (r) of 0.729 and a coefficient of determination (r²) of 0.532, meaning 53.2% of the performance variation is influenced by training. Simultaneously, competence and training have a strong and significant influence on performance, with a correlation coefficient (R) of 0.763 and a coefficient of determination (R²) of 0.582, indicating that 58.2% of the performance variation of IBS nurses at RSUD Ciawi is determined by these two variables. Therefore, continuous improvement of competence and training can serve as an important strategy to enhance nurse performance in the Central Surgery Installation of RSUD Ciawi.